Combined effects of host genetics and diet on human gut microbiota and incident disease in a single population cohort - Qin, Youwen; Havulinna, Aki S.; Liu, Yang; Jousilahti, Pekka; Ritchie, Scott C.; Tokolyi, Alex; Sanders, Jon G.; Valsta, Liisa; Brożyńska, Marta; Zhu, Qiyun; Tripathi, Anupriya; Vázquez-Baeza, Yoshiki; et al. (Nature genetics, 2022)
Human genetic variation affects the gut microbiota through a complex combination of environmental and host factors. Here we characterize genetic variations associated with microbial abundances in a single large-scale population-based cohort of 5,959 genotyped individuals with matched gut microbial metagenomes, and dietary and health records (prevalent and follow-up). We identified 567 independent SNP–taxon associations. Variants at the LCT locus associated with Bifidobacterium and other taxa, but they differed according to dairy intake. Furthermore, levels of Faecalicatena lactaris associated with ABO , and suggested preferential utilization of secreted blood antigens as energy source in the gut. Enterococcus faecalis levels associated with variants in the MED13L locus, which has been linked to colorectal cancer. Mendelian randomization analysis indicated a potential causal effect of Morganella on major depressive disorder, consistent with observational incident disease analysis. Overall, we identify and characterize the intricate nature of host–microbiota interactions and their association with disease. Genome-wide association analysis of gut microbial taxa in a single homogenous population-based cohort of 5,959 Finnish individuals identifies 567 independent SNP–taxon associations, including strong associations with LCT , ABO and MED13L .